The impact of non-monetary rewards on employee retention in Malaysia SMEs - Lee, Jia Zet (2024)
Nowadays, employee retention has become a critical challenge for organisations, especially in the context of SMEs in Malaysia. As monetary rewards have slowly lost their power of influence to retain employees in one organisation, followed by the change in working patterns and employee behaviour in the workplace, non-monetary rewards now play a crucial role. Therefore, this study sought to identify the impact of non-monetary rewards towards employee retention in Malaysian SMEs, particularly in flexible working arrangements, career development, recognition, and fringe benefits. In order to examine the relationship between flexible working arrangements, career development, recognition, and fringe benefits with employee retention in Malaysian SMEs, quantitative research through the distribution of questionnaires to eight Malaysian SME companies has been conducted. A sample size of 165 participants who worked in the eight selected SME companies was involved in this research to provide their opinions and insights by referring to their experiences in current work. Furthermore, the SPSS system was used to conduct data analysis, including preliminary tests, descriptive, correlation, and regression analysis. After the analysis, the findings suggest that career development and fringe benefits have a positive impact towards employee retention in Malaysian SMEs, while flexible working arrangements have a reverse relationship. For recognition, it was found to be not significant in this study. On top of that, among the two independent variables that contribute to a positive relationship, career development stands as the most significant influence towards employee retention. Finally, from the results obtained, it hopes to provide valuable insights to the HR practitioners in SME companies a focal point to be emphasized in order to better retain their employees and thus reduce turnover costs.